A Novel Mutation in the Thyroid Hormone Receptor Beta-Gene in a Patient Who Developed Thyroid Nodules - Hidalgo Coronado, Lorena (2019)
Background: Thyroid hormone Resistance (THR) is a genetic disorder characterized by decreased tissue sensitivity to thyroid hormones (THs). The key finding is the presence of high concentrations of THs in the presence of non-suppressed TSH. Clinical phenotype is highly variable since signs of hormone deficiency, sufficiency and excess could coexist. High TSH produces goiter, being the most common feature. It has been associated with increased risk of developing thyroid nodules, with malignancy risk. Management of nodules associated with THR is as other nodules, with fine-needle aspiration guided by ultrasound (US) as first approach and ATA recommendation of surgery in children when Bethesda category is III or higher.